Functional and phylogenetic diversity of scattered trees in an agricultural landscape: Implications for conservation - Athayde, Eduardo Anversa [UNESP]; Cancian, Leonardo Farage [UNESP]; Verdade, Luciano Martins; Morellato, Leonor Patrícia Cerdeira [UNESP] (Elsevier B.V., 2015)
Scattered trees are an important feature of the matrix of agricultural landscapes, but their role in biodiversity conservation is still controversial and largely unexplored. We aim to investigate the value of scattered trees to maintain the functional and phylogenetic diversity within the matrix of an agricultural landscape dominated by commercial Eucalyptus plantation in southeastern Brazil. For this, we established a grid of 100 x 100 m cells covering the full extent of a farm, conducted an inventory and georeferenced all scattered trees present within each cell in the grid. Further, we modeled the spatial distribution of the taxonomic, functional and phylogenetic diversity of trees in the farm. Scattered trees presented lower taxonomic, phylogenetic and functional diversity than the native vegetation nearby, and these diversity indices were strongly related to local species richness. However, the scattered trees held 64% and 85% of the total functional and phylogenetic diversity in agricultural land use, respectively. Further, the scattered trees maintained higher functional and phylogenetic diversity levels in agricultural land use than expected for random assemblages of species. Scattered trees in the landscape are unprotected by Brazilian environmental laws since they are not included in any network of protected areas. Here we demonstrated the importance of conservation of scattered trees to reduce the loss of phylogenetic and functional diversity in agricultural landscapes, counteracting the loss of species that occurs in highly productive agroecosystems.
Keywords: Biodiversity conservation; Remnant trees; Isolated trees; Eucalyptus plantation